Real-world retrospective cohort study of three conversion therapy regimens for unresectable locally advanced pancreatic cancer: a single-center 5-year analysis focused on conversion resection rate and survival outcomes - He, Rui-Zhi; Zhou, Min; Chen, Yong-Jun; Guo, Xing-Jun (Translational Cancer Research, 2026)
Background: Locally advanced pancreatic cancer (LAPC) is mostly unresectable at initial diagnosis. Conversion therapy has become core treatment to downstage tumors for radical resection, yet consensus on optimal first-line regimen remains lacking. This real-world study compared three mainstream conversion regimens and identified independent survival predictors to guide individualized treatment.Methods: A single-center retrospective cohort of 172 unresectable LAPC patients receiving gemcitabine plus nab-paclitaxel (AG), modified FOLFIRINOX (mFOLFIRINOX), or AG sequential chemoradiotherapy (CRT) from 2019 to 2023 was enrolled. Tumor conversion, surgical, survival and safety outcomes were analyzed. Cox regression was adopted to screen independent prognostic factors, with P